A model for the delamination kinetics of La0.8Sr0.2MnO3 oxygen electrodes of solid oxide electrolysis cells - Zhang, Y.; Chen, Kongfa; Xia, C.; Jiang, San Ping; Ni, M. (Elsevier Ltd, 2012)
A theoretical model is developed to simulate the delamination kinetics of La0.8Sr0.2MnO3 (LSM) electrode from YSZ electrolyte in solid oxide electrolysis cells (SOECs). The delamination is caused by the total stress including the internal oxygen pressure in LSM near the electrode/electrolyte interface, and the tensile stress by the oxygen migration from the YSZ electrolyte to LSM lattice. Weibull theory is used to determine the survival probability of electrode/electrolyte interface under the total stress. The relaxation time corresponding to the time for oxygen diffusion from the interface to the microcracks in La0.8Sr0.2MnO3 links the survival probability with polarization time, thus the survival interface area can be predicted with varying anodic polarization time. The model is validated with experimental data. The effects of applied anodic current and operating temperature are discussed. The present model provides a starting point to study more complex cases, such as composite oxygen electrodes.